Preterm Gestation Along with Partial Hydatidiform Mole and Alive Foetus - Tamrakar, S R; Chawla, C D (Kathmandu University Medical Journal, 2012)
Gestational trophoblastic disease encompasses a diverse group of lesion. If molar changes in the placenta are known along with an alive fetus then the situation is difficult to manage. We present successfully managed case of partial degeneration of placenta in molar pregnancy with an alive fetus at second stage of preterm labour. DOI: http://dx.doi.org/10.3126/kumj.v9i3.6310 Kathmandu Univ Med J 2011;9(3):222-4